أصول المصادر في المعرفة: دراسة منهجية - Hasan Mohammed Alasmary (Universitas Negeri Jakarta, 2019)
The knowledge theory is an important discussion and the most important theme of these theories is about the source of knowledge, which received a broad debate in modern Western thought. It has become excessive because of its drawback behind the secular visions, in some sources, such as reason and sense, as well as marginalization of flaws in thought at all times and places. One of the ways to deal with this issue: promoting moderatism in ideas and thoughts that lead to justice and excellence. The research methodology is based on a combination of analytical, structural, and critical approaches. The results highlight the importance of finding sources of knowledge, there is no knowledge without sources, the importance of determining the scope work of each source, examining the sources through five aspects, which are information, logic, sense, persons, and intuition. By looking at the sources integrally, and that religion should become the source of knowledge because it comes from a divine revelation. Sources of knowledge that come from human will not be useful unless they are related to the light of revelation.